Brain Transcriptome Profiling Analysis of Nile Tilapia (Oreochromis niloticus) Under Long-Term Hypersaline Stress - Liu, Yan; Li, Erchao; Xu, Chang; Su, Yujie; Qin, Jian G.; Chen, Liqiao; Wang, Xiaodan (Frontiers in Physiology, 2018)
The fish brain plays an important role in controlling growth, development, reproduction and adaptation to environmental change. However, few studies stem from the perspective of whole transcriptome change in a fish brain and its response to long-term hypersaline stress. This study compares the differential transcriptomic responses of juvenile Nile tilapia (Oreochromis niloticus) maintained for eight weeks in brackish water (16 practical salinity units, psu) and in freshwater. Fish brains from each treatment were collected for RNA-seq analysis to identify potential genes and pathways responding to hypersaline stress. A total of 27,089 genes were annotated, and 391 genes were expressed differently in the salinity treatment. Ten pathways containing 40 differentially expressed genes were identified in the tilapia brain. Antigen processing and presentation and phagosome were the two principally affected pathways in the immune system. Thirty-one of 40 genes were involved in various expressions associated with environmental information processing pathways such as neuroactive ligand-receptor interaction, cytokine-cytokine receptor interaction, the Jak-STAT signaling pathway, cell adhesion molecules (CAMs), and the PI3K-Akt signaling pathway, which are the upstream pathways for modulation of immunity and osmoregulation. The most-changed genes (>5-fold) were all down-regulated, including four growth hormone/prolactin gene families, i.e., prolactin precursor (-10.62), prolactin-1 (-11), somatotropin (-10.15), somatolactin-like (-6.18), and two other genes (thyrotropin subunit beta (-7.73) and gonadotropin subunit beta-2 (-5.06)) that stimulated prolactin release in tilapia. The downregulation pattern of these genes corroborates the decrease in tilapia immunity with increasing salinity and reveals an adaptive mechanism of tilapia to long-term hypersaline stress. Ovarian steroidogenesis, isoquinoline alkaloid biosynthesis, and phenylalanine metabolism are the three important pathways in the response of the fish to long-term hypersaline stress. This study has identified several pathways and relevant genes that are involved in salinity regulation in a euryhaline fish and provides insight into understanding regulatory mechanisms of fish to salinity change.